A computational model for water use efficiency in rice production. - Jaafar, Mahmad Nor; Saad, Puteh; V. Arjunan, Satya Nanda (Penerbit UTM Press, 2000)
Rice farming is somewhat sentimental and many of the hard facts that intertwined with the complexity of farming are often taken for granted. The interrelationship of water use in the soilÂ¬crop-atmosphere with respect to the farming practices, the availability and economic, of water, the input cost and the profitability on rice production are attributes of this complexity. In the context of globalize trade and modernization, rice farming has to be not only more commercial but eco-efficient as well. The use of information technology (IT) to solve the burning issues of limited resource and the role of water to garnish the limited land for greater output of rice with minimum of capital input and environmental degradation is warranted. This paper present a model that address the efficiency of water use in rice production, allowing users to trends the possible limits, giving an intuitive feeling and what if situation in several probable scenarios. It explicitly deals with the aspect of water productivity due to variation in farming practices, giving tangible values relating yield, water use and its economics implication. ii works on the frameworks of the boundary limit of the components of water balance at farm level, yield from crop varieties and farming practices adopted. The model is built using Visual C++ version 6 as the programming language and the model is implemented on Windows 95/98 platform. Managers and policy makers will use the model as DSS to make fair judgements on the value of water in rice production and realistic water use efficiency limit.